THE ROLE OF ETHICAL SCHOOL SUPERVISION IN BUILDING A NEW AND A BETTER NIGERIA (Journal of Association of Educational Management and Policy Practitioners, 2026)
The paper explores the significance of ethical supervision in Nigeria's education sector, emphasizing its transformative potential in nation-building. Using relevant theoretical perspectives, the study examines how ethical conduct among school supervisors influences school effectiveness, student achievement, and long-term national development. The conceptual review highlights ethical principles, challenges in current supervision practices, and the nexus between education and sustainable development. The paper argues that fostering a culture of integrity, accountability, and professionalism in school supervision can strengthen educational delivery, reduce corruption, and nurture responsible citizens who are essential to a new and better Nigeria. The paper recommended policy reforms, training, and leadership models that embed ethical values in the supervisory process